Comparative Analysis of geomorphosites in volcanoes of Costa Rica, Mexico, and Spain - Pérez Umaña, Dennis (2019)
This study is a comparative analysis of geomorphosites in Poás volcano in Costa Rica, Paricutín volcano in Mexico, and Teide Pico Viejo volcanoes in Spain. The main objective of the paper is to compare the geomorphosites of these volcanoes using a geomorphosites evaluation to define which volcano is better for touristic activity. In this study, the geomorphosites evaluation methodology of Serrano and González (Geomorphologie: Relief, Processus, Environment 3:197–208, 2005) was used. The study shows that these volcanoes have many different geomorphosites with geological and cultural importance for the population and that these characteristics make touristic development possible. One of the conclusions of this paper is that these volcanoes are representatives of the nations of Costa Rica, Mexico, and Spain, with interesting cultural and geological characteristics and unique landscapes. The methodology used gives another perspective to study the topographic setting and presents ideas to make new touristic sites available and attractive in other locations.